From social action to business action - A qualitative research on the professionalization process of a blogger: Case P.s. I Love Fashion -blog - Nikkanen, Elina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Blogging is one of the most common forms of social media today. Blogs have become a powerful media and bloggers are settled stakeholders to marketers. Commercialization of the blogosphere has enabled an increasing number of bloggers professionalize and blog as a full-time occupation. The purpose of this study is to understand the professionalization process of a blogger from an amateur blogger to a professional actor. The following sub-questions were used to further elaborate the topic: What have been the meaningful events and developments fostering professionalization? What are the prerequisites for popularity in blogging? Are there any key success factors to acknowledge in order being able to make business out of your blog? The theoretical framework of this study was formed based on the two chosen focus areas for professionalization; social drivers and business drivers. The theoretical framework is based on literature from fields of marketing and social sciences, as well as previous research on social media, blogging and professionalization. The study is a qualitative case-study and the research data was collected in a semi-structured interview. The case chosen to this study is a lifestyle-blog. The writer of the case blog has been able to develop her blog to become a full-time professional blogger. Based on the results, the professionalization process of a blogger is not a defined process, but instead comprised of coincidental events as well as considered advancements. Success in blogging is based on the bloggers own motivation and passion for writing and expressing oneself in the form of a blog, instead of a systematic construction of a successful career in blogging. Networking with other bloggers as well as affiliates was seen as an important success factor. Popularity in the blogosphere and a high number of followers enable professionalization, as marketers actively seek to collaborate with popular bloggers with strong personal brands. Bloggers with strong personal brands are especially attractive due to their opinion leadership in their reference group. A blogger can act professionally either as entrepreneur or blogging for a commercial webpage. According to the results of this study, it is beneficial for the blogger’s professional development as well as career progress, to act on different operating models